Evaluasi Kinerja Tenaga Kerja Bagian Sortasi Biji Pinang Areca catechu, L.) CV. ABC Berdasarkan Faktor-Faktor yang Berpengaruh - Arsil, Fikri; Santosa, Santosa (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2020)
Evaluation of influential factors to labors productivity will get the recommendation on human resource development and increase labors performance by company. The aim of this research to know about the effect on motivation, working environmental, salary, working responbility, and lifespan ofareca nuts sorting labors in CV. ABC based on influental factors. The research uses survey method and doubled linear regression analysis for data processing. The result shows that motivation, working environmental, salary, working responbility, and lifespan have effect on sorting labors in CV. ABC with doubled linear regression analysis is Y = -4,640 + 0,210 X1 + 0,089 X2 + 0,080 X3 - 0,070 X4 + 0,813 X5. This equality shows coefficient value from lifespan variable is biggest, it is 0,813. Thus, evaluation to sorting labors get 5 recommendations for increasing labors performance.